Exploiting microbubble-microbe synergy for biomass processing: Application in lignocellulosic biomass pretreatment. (October 2016) - Mulakhudair, Ali R.; Hanotu, James; Zimmerman, William
Abstract : Abstract The potential of lignocellulosic biomass as a sustainable biofuel source is substantial. The development of an efficient and cost effective pretreatment approach remains challenging. In this study, we have explored a new, relatively cheap pretreatment option that works at ambient temperatures. By using microbubbles generated by fluidic oscillation, free radicals around the gas-liquid interface of the microbubble readily attack and degrade lignocellulosic biomass, rendering it more amenable to digestion. The combination of microbubbles and Pseudomonas putida —a robust delignification and cellulolytic microbe, further improved biomass degradation and consequently, increased glucose production from wheat straw in comparison to solo pretreatment of the biomass with microbubbles and Pseudomonas putida respectively. The microbubble-microbe approach to make biomass more amenable to sugar production is potentially a valuable alternative or complementary pretreatment technique. Highlights: Microbubble generate free radicles that attack and degrade biomass in general and lignin in particular. Pseudomonas putida releases cellulolytic enzymes, which are more influential in glucose production than microbubble effect. The microbubble-microbe pretreatment technique brought about both physical and chemical alterations to the biomass structure. The microbubble-microbe synergy is more effective and efficient than either solo option for pretreatment of lignocellulosic biomass.